2021
DOI: 10.1080/13814788.2021.1982889
|View full text |Cite
|
Sign up to set email alerts
|

To prevent being stressed-out: Allostatic overload and resilience of general practitioners in the era of COVID-19. A cross-sectional observational study

Abstract: Background Responsibility of general practitioners (GPs) in delivering safe and effective care is always high but during the COVID-19 pandemic they face even growing pressure that might result in unbearable stress load (allostatic overload, AO) leading to disease. Objectives We aimed to measure AO of Hungarian GPs during the COVID-19 pandemic and explore their recreational resources to identify potential protective factors against stress load. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…Although studies showed the mental health of students, trainees and faculty have suffered from the impact of COVID-19 [ 2 , 4 , 35 , 36 ], our results show that working in a training practice lowered the risk of adverse mental health events. This effect persists even after controlling for having a multidisciplinary team, the respondent’s years of experience in primary health care, number of GPs in the practice, urban or rural location and function of the respondent in the practice (GP or GP trainee).…”
Section: Discussioncontrasting
confidence: 65%
“…Although studies showed the mental health of students, trainees and faculty have suffered from the impact of COVID-19 [ 2 , 4 , 35 , 36 ], our results show that working in a training practice lowered the risk of adverse mental health events. This effect persists even after controlling for having a multidisciplinary team, the respondent’s years of experience in primary health care, number of GPs in the practice, urban or rural location and function of the respondent in the practice (GP or GP trainee).…”
Section: Discussioncontrasting
confidence: 65%
“…Time pressure is a common stressor in general practice and negatively affects the GP seeking relevant information and reading scientific literature [31,32]. During a pandemic, increased time pressure due to a higher workload, uncertainties regarding an unknown disease, work reorganization, and potential lack of confidence in caring for COVID-19 patients might underpin additional psychological distress among GPs [33][34][35][36][37][38][39]. Time pressure has been recognized as one of the workplace challenges with a negative impact on GPs' professional resilience [22].…”
Section: Discussionmentioning
confidence: 99%
“…Carga alostática y estrés laboral: una revisión integrativa BIOMARCADORES PRIMARIOS DEL ÍNDICE DE CARGA ALOSTÁTICA Dos estudios 27,30 no utilizaron biomarcadores para calcular el índice de carga alostática, en vez de ello, utilizaron el índice clínimétrico de Fava et al 32 , adaptado del índice psicosocial. La medición de al menos un biomarcador primario de carga alostática (DHEA, cortisol, norepinefrina y epinefrina) estuvo presente en el 60% de las investigaciones, excluyendo los estudios clínimétrico puros.…”
Section: -9unclassified
“…El índice psicosocial (psychosocial index, PSI) 34 fue usado en dos estudios 27,30 para reemplazar biomarcadores clínicos, teniendo en cuenta los siguientes pasos: el criterio A consiste en la identificación del factor estresante o de la amenaza contextual detonante del estrés, factores no controlados e imprevistos que persisten en el tiempo, por ejemplo, pérdida de una persona importante, pérdida de la salud, conflictos laborales y familiares entre otros, sin desconocer que algunas situaciones de la vida cotidiana pueden superar los mecanismos de afrontamiento del individuo y convertirse en factores estresantes. El segundo punto de los criterios, o el criterio B, implica las manifestaciones clínicas, que pueden incluir síntomas psicológicos, deterioro en el funcionamiento social y ocupacional.…”
Section: Test De Estrésunclassified